The Impact of Direct Compensation Towards Employees’ Performance at Opal Coffee Cafe & Resto Medan - Benny Lim; Bestadrian Prawiro Theng; Felix Leonardi; Susanto; Afridayanti Surbakti (Universitas Muhammadiyah Palu, 2025)
One of the most important factors that could be developed is the element of employees. In order to reach the goals and target, the companies should not only pay attention on their profits, but also to the employee’s welfare and work effective and efficiently. Employees play vital role in bringing about the process of production/ process. Therefore, a fair and attractive compensation system is a must for every business and organization. The happy employee will results in good performance. Direct compensation refers to monetary benefits offered and provided to employees in return of the services they provide to the organization. The writer did observation in the shop and the writer found out that the employees’ performance is not good. They have lack (finish their reports slowly and low discipline where the employees leave the office on time and rarely want to spend much more time in the restaurant to do other additional jobs. The writer will use the total population in Opal Coffee Cafe & Resto Medan which is 32 employees. The writer uses Arikunto Sampling theory. The sample size is 32. The writer uses census sampling technique which the writer takes all population as sample. In analyzing data, the writer used some methods such as data descriptive, the validity test, the reliability test, the correlation test, the determination test,linier regression, and the hypothesis test. According to the result calculation data through the answers of the respondents, the writer got the result of 0.602 which means direct compensation has a strong relation or impact towards employees’ performance at Opal Coffee Cafe & Resto Medan. From the calculation of determination test, the writer got zcount=3.34. The zcount > ztable (3.34> 1.96), This means the Null hypothesis (Ho) is rejected. The writer can conclude that direct compensation has impact towards Employees’ performance at Opal Coffee Cafe & Resto Medan.